A new proposed cloud computing based architecture for space ground data systems. (2018) - Kaddouri, Ali; Guezouri, Mustapha; Mbarek, Nader
Many companies decided to move towards the cloud computing technology in order to manage, monitor and explore huge space data amount in the space ground data systems. The corresponding transition adaptation needs a study to classify each space related service in the appropriate cloud computing service model layer; SaaS, PaaS and IaaS. In this paper, we specify a representation of proposed cloud computing based ground data system architecture for earth observation missions. The proposed architecture takes into consideration the collaboration aspect between multiple space agencies. We evaluate the time, storage and processing performance when using the cloud computing environment. The obtained results show a good performance where contact time increases significantly and more data was processed compared to the classic approach using hard CPU units. These results and especially the obtained contact time increase provide multiple agencies with more opportunities to intervene in cases of anomalies or disaster.